Implementation of supine percutaneous nephrolithotomy: a novel position for an old operation - Sofer, Mario (Cent European J Urol, 2017)
INTRODUCTION: Supine percutaneous nephrolithotomy (PCNL) has become increasingly widespread during the last 2 decades. The aim of this study was to analyze the transition from prone to mainly supine PCNL in 2 endourologic centers. MATERIAL AND METHODS: We retrospectively analyzed data on 214 consecutive supine PCNLs divided into the first (2011–2013) and last (2014–2016) 3 years of this study. The first 27 cases were also included in a randomized controlled trial (RCT) by comparison with 24 prone PCNLs. We compared the clinical outcome and implementation rate. The surgical team was surveyed for their overall impression of performing supine PCNLs. RESULTS: The RCT revealed a trend toward shorter operative time (138 vs. 150 minutes), anesthesia time (174 vs. 192 minutes) and hospitalization (2.2 vs. 2.6 days) in the supine PCNL group, without statistical significance and similar stone free rates (SFR) as for the prone PCNL group. Implementation of the supine PCNL reached 96% in 3 years. There was a decrease in operative time (110 vs. 154 minutes; P <0.0001), hospital stay (1.5 vs. 2.1 days; P <0.01), blood transfusion (5% vs. 14%; P <0.05) and rate of ancillary procedures (5% vs. 16%; P <0.05) in the last 3 years of the study. SFR remained stable. Both the surgeons and anesthesiologists expressed their unanimous preference for the supine position over the prone position. CONCLUSIONS: Supine PCNLs are easy to implement without a significant learning curve for an experienced endourologist. They can be employed in complex cases and improve surgeon's ergonomics and anesthesiologist's access to the patient.